2020
DOI: 10.18805/ijar.b-4174
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Prediction Models for Estimation of Pre-weaning Body Weight of Pigs using Morphometric Traits

Abstract: Background: In the present study, a set of non-linear prediction equation was developed using records of body measurement traits, namely heart girth, punch girth, height at shoulder, height at back, height at fore leg, height at back leg and body length of pigs. Repeated measurement of traits at birth, 15 d, 30 d and weaning (42 d) of 394 piglets were used. Methods: The regression of body weight on body measurement traits showed non-linear relationship based on equation, Y = aXb. Correlation of heart girth wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…From Fig 3, there was a positive correlation between growthrelated factors and body weights, specifically the height of pig (HP), age (AG), length (LP) and girth length (GL). Other researchers have reported similar findings, in where FI (Pierozan et al, 2016), DW (Arulmozhi et al, 2020), HP (Yang et al, 2019), AG (Birteeb et al, 2015), LP (Banik et al, 2021), GL (Banik et al, 2021) and RCO 2 (Basak et al, 2022) are highly associated with pig's body weight. In addition, a negative correlation existed between PBW and the pig's body temperature (PBT).…”
Section: Input Variables Selectionsupporting
confidence: 60%
“…From Fig 3, there was a positive correlation between growthrelated factors and body weights, specifically the height of pig (HP), age (AG), length (LP) and girth length (GL). Other researchers have reported similar findings, in where FI (Pierozan et al, 2016), DW (Arulmozhi et al, 2020), HP (Yang et al, 2019), AG (Birteeb et al, 2015), LP (Banik et al, 2021), GL (Banik et al, 2021) and RCO 2 (Basak et al, 2022) are highly associated with pig's body weight. In addition, a negative correlation existed between PBW and the pig's body temperature (PBT).…”
Section: Input Variables Selectionsupporting
confidence: 60%
“…This result may be obtained due to Gompertz (1825), yt = Ae -bexp (-kt) t Brody (1945), yt = A (1 -be kt ) t Von Bertalanffy (1957), yt = A (1 -be kt ) 3 t the used of younger animals live weight data at the time of study. Similar factors were explained for fluctuation of asymptotic weight of Nelore cows for both Gompertz and von-Bertalanffy models (Forni et al, 2009;Garnero et al, 2005;Banik et al, 2020). Using the estimates of the parameters of the non-linear models, crossbreds can be selected from the maturity rate, because, crossbred with higher maturity rates was earlier than RCC and ND, those showed lower maturity rates in Brody and von Bertalanffy models.…”
Section: Model Parametersmentioning
confidence: 83%
“…Several studies have reported the relationships between morphological traits and body weight in pigs. Path coefficients indicate that foreleg height, body length, and heart and belly circumference lengths are important indicators for determining preweaning live body weight in pigs (Banik et al, 2021). In addition, for pigs that exceeded 40 kg, body length, heart girth, and body height parameters were identified as the best representative traits for predicting body weight with an R 2 value of 0.92 in the developed regression model (Valugembe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%